2015
DOI: 10.1039/c5ra12558h
|View full text |Cite
|
Sign up to set email alerts
|

Size dependent magnetic hyperthermia of octahedral Fe3O4 nanoparticles

Abstract: Octahedral Fe3O4 nanoparticles show a wide size range for high SAR values to be used as an excellent thermal seed for magnetic hyperthermia cancer treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
44
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(52 citation statements)
references
References 44 publications
5
44
0
3
Order By: Relevance
“…Previous reports showed that magnetic properties of iron oxide nanoparticles such as saturation magnetization (M s ), specific absorption rate (SAR), and relaxivity (r 2 ) have a close relationship with their sizes among a large size range from a few nanometers to hundreds of nanometers [2,[13][14][15][16][17]. Tong et al [16] reported that the M s of MION increased slightly with size from 6 to 40 nm, and the SAR values increased monotonically with size enlarged (325 kHz, 20.7 kA/m), while SAR was really low for MION below 11 nm.…”
Section: Introductionmentioning
confidence: 99%
“…Previous reports showed that magnetic properties of iron oxide nanoparticles such as saturation magnetization (M s ), specific absorption rate (SAR), and relaxivity (r 2 ) have a close relationship with their sizes among a large size range from a few nanometers to hundreds of nanometers [2,[13][14][15][16][17]. Tong et al [16] reported that the M s of MION increased slightly with size from 6 to 40 nm, and the SAR values increased monotonically with size enlarged (325 kHz, 20.7 kA/m), while SAR was really low for MION below 11 nm.…”
Section: Introductionmentioning
confidence: 99%
“…The resulting Fe–OCH 2 R species reacted with other Fe compounds to form Fe–O–Fe bonds, and the continuous formation of the Fe–O bonds by the thermal decomposition led to the generation of Fe 3 O 4 seeds . During the thermal decomposition process of Fe(acac) 3 , 1‐hexadecanol decomposed to 4‐hydroxy‐5‐methyl‐pentan‐2‐one and 1‐hexadecanyl acetate, which produced reductive environments . The reduction of M(acac) 3 (M = Fe, Co, Mn) induced by oxidative decomposition of surfactants was studied well in the literature .…”
Section: Resultsmentioning
confidence: 99%
“…Besides, the Fe 3 O 4 nanocrystals have low remanence values of about 4.78, 5.97, and 10.5 emu/g. Generally, the saturation magnetization (M S ) is expected to increase with an increasing particle size . However, the M S value of porous Fe 3 O 4 nanocrystals decreased with the increasing particle size of the nanocrystals.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[4] For additional biocompatibility issue or specific hydrophilic properties most of the time a polymer layer like polyethylene glycol (PEG) is coated on it. Y Lv et al [5] prepared magnetite nanoparticles of different sizes using thermal decomposition technique [6]. In magnetic hyperthermia, the SPIONs are injected into the body intravenously and driven to the cancerous tumor cells with the help of external magnetic field or the specific agents that can be capped on the particles find its way to the tumor itself.…”
Section: Iron Oxide Nanoparticles For Magnetic Hyperthermiamentioning
confidence: 99%